Edukasi Kepatuhan Minum Obat Pada Lansia Dengan Hipertensi Di Posyandu Lansia Desa Baliase - Ismunandar Wahyu Kindang; Moh. Malikul Mulki; Rahmat Doko; Ni Nyoman Elfiyunai (CV. Multi Kreasi Media, 2024)
Non-compliancewith taking antihypertensive drugs is a major problem for people with hypertension. This is what triggers the progesivity of hypertension in other organs such as the heart and kidneys. Non-adherence to antihypertensive medication can affect up to 80% of the progression of hypertensive disease and become a major problem in controlling blood pressure. Low adherence to hypertension treatment correlates with increased blood pressure prognosis of hypertensive disease. ISH (International Society of Hypertension) recommends the importance of adherence to antihypertensive treatment globally in order to control optimal blood pressure. Hypertension cannot be cured but can be controlled through routine health control, and taking medication regularly to reduce the risk of complications. The success of hypertension treatment cannot be separated from the knowledge, attitude and adherence of someone taking drugs. One effective action to prevent the occurrence of complications of hypertension is education. Education on adherence to taking drugs like this is sought to be a continuous activity so that it can increase public knowledge regarding the importance of adherence levels in taking antihypertensive drugs so that the outcome of treatment therapy can be achieved, besides that after educating hypertensive patients are able to apply a healthy lifestyle and can also utilize materials from nature to treat hypertension.